STUDENTS’ LANGUAGE ATTITUDES TOWARDS THE MAINTENANCE OF HERITAGE LANGUAGE - Tatu Zakiyatun Nufus (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Language attitude is one of the most important things in learning language. It determines students’ seriousness towards language acquisition, this research investigates students’ language attitude towards their heritage language and other languages that they acquire and learn, the study use qualitative approach with descriptive analysis, and 20 students with different language heritage and culture were surveyed through questionnaires and interview, this study will investigate the students’ language attitude towards their heritage language and other languages they acquire and learn and how valuable are those languages to them? (What are the values of each language?), the result demonstrates that students’ language attitudes toward acquisition or maintenance of heritage language among students is relatively good. They use Bahasa Indonesia, and other language (Arabic and English) in daily communication in a weekday, while the heritage language used only in their holiday when they meet with parents and other family, to support other language acquisition, the school establish language policy that relate to language use at that school. In maintaining the heritage language, the students use it in their home to interact among family members during holiday from school activity. Finally, the study above has wide pedagogical implication for learning and teaching language for students, it implies that teaching language to students should be in line with students’ need. And the use of heritage language and foreign language should be balanced among them, therefore, the student’s language attitudes will grow faster and better.